Evaluation of Outcome of Clavicle Fractures Managed with Locking Plates - C Ramesh Harish (Asian Journal of Medical Research, 2016)
Introduction: To evaluate outcome of clavicle fractures managed with locking plates. Subjects and Methods: Seventy patients of clavicle fractures of either gender was enrolled in the study. Open reduction and internal fixation was done using a 3.5 mm locking plate with lateral extension. The postoperative pain was assessed using Visual Analogue Scale (VAS) on postoperative days 1, 3 and 10. The functional outcome was assessed at the end of 2nd and 6th month with the help of Disabilities of the Arm, Shoulder and Hand (DASH) scoring. Results: Out of 70 patients, males were 40 (57.1%) and females were 30 (42.9%). Side involved was right in 28, left in 22 and both in 20. Mode of injury was RTA in 42, fall in 20 and violence in 8 cases. The difference was significant (P< 0.05). The mean VAS on day 1st was 5.8, on day 3rd was 3.0 and on day 10th was 0. DASH at 2 months was 12.1 and at 6 months was 4.9. The difference was significant (P< 0.05). Functional outcome was excellent in 52, good in 11 and moderate in 7 cases. The difference was significant (P< 0.05). Conclusion: The management of distal end clavicle fractures with compression plating resulted superior outcome.